Editorial for Vol. 35, No. 2 - Juwon Lim (Hanggong uju uihakoeji)
This issue of the Korean Journal of Aerospace and Environmental Medicine (Vol. 35, No. 2) presents five studies advancing flight safety and crew health. A design effort with 10 senior captains proposes multi-parameter auditory alerts and automatic goaround logic, projected to avert 26% of unstable-approach accidents. A cross-sectional study of 180 Korean cockpit and cabin crew details post-Coronavirus disease 19 symptoms—fatigue, cough, myalgia—and shows normal-weight staff recover more slowly; ≥5 symptoms predict delays beyond 4 weeks, stressing individualized returnto- flight surveillance. A scoping review of 53 domestic fatigue papers documents a post-2010 surge, heavy survey reliance, and calls for biologic monitoring and big-data Fatigue Risk Management Systems. An ophthalmic review links cabin low humidity, mild hypoxia and cooling to tear-film instability, reporting dry-eye prevalence of 20% in passengers and 27.8% in crew and recommending hydration, airflow control and lipidbased lubricants. Finally, a virtual case-anchored appraisal shows coronary computed tomography angiography plus calcium scoring refine risk stratification for pilots with coronary disease and support graduated recertification. Together, these articles deliver actionable evidence for regulators, operators and aerospace clinicians and enrich clinical practice.